Sosialiasi Peningkatan Kesadaran Generasi Muda atas Bahaya Dampak Lingkungan Sampah Masker Medis Bekas akibat Pandemi Covid-19: Pengmas Departemen HI FISIP UNAIR di Desa Sukorejo, Kecamatan Bangorejo Kabupaten Banyuwangi - Siti Rokhmawati Susanto (Universitas Negeri Padang, 2022)
The global Covid-19 pandemic has not only raised health issues which have become a big problem, but it has also created complex problems for the international community,such as health, economic unproductivity, and changing patterns of social interaction. Another significant problem that also emerges is an environmental issue, referring to the increasing number of used medical mask waste coming from societies in order to anticipate the virus. This problem is getting more serious as medical mask waste contains plastic waste, where its decomposition takes decades. In order to provide a solution to the increasing waste of used masks, the involvement of the youth is necessary because young people have many positive capacities, compared to others. Therefore, Department of International Relations, Universitas Airlangga establishes apartnership with Madrasah Aliyah Al Huda and Karang Taruna Suka Karya, in the Sukerejo Village, Bangorejo District, Banyuwangi Regency, in a hybrid way. This aims to increase the awareness among youth to manage the waste of used mask waste in more proper procedures, so it will not cause negative impact to the environment.